Empowerment Practices of Independent Palm Sugar Farmers Through the CSR Program of PLN Nusantara Power Up Paiton - Ananda Satria Oka Yudha; Javas Yola Bhagawanta; Ibnu Magroho; Eko Rohim (Global Writing Academica Researching and Publishing, 2025)
This research focuses on the implementation of the Independent Aren Farmer Program in Kalianan Village. This research aims to explain the CSR implementation of PT PLN Nusantara Power Unit Pembangkitan Paiton, especially in community empowerment activities. The background issues addressed by the program in Kalianan Village include the safety of palm sugar farmers during the tapping process, the underutilization of cattle waste, and limited market access for processed palm sugar products. On the other hand, the village’s main potential includes the presence of 137 palm sugar farmers capable of independent production, product diversification, and employing data collection techniques such as observation, interviews, and documentation. The research was compiled using descriptive qualitative methods and used data collection techniques through observation, interviews, and documentation. Data analysis was conducted based on the Triple Bottom Line concept. The impact of the PAMAN program includes social, economic and environmental aspects. The Garuda Sakti group as the beneficiary of the program, is expected to be able to implement the program independently and for a long time. This is a measure of the company’s success in implementing community empowerment activities in Kalianan Village.